Mechanism of translocon function: current insights and models - Driessen, Arnold (Henry Stewart Talks, 2008)
Bacterial protein sorting, Evolutionary conserved translocons, Structure of SecYEG complex, Oligomeric assemblies of the SecYEG complex, Oligomeric state of the active SecYEG complex, Orientation of the SecYEG in dimeric complexes, Active or passive role of ribosome and SecA during channel opening
Updated at 2021/03/03